Douglass North as a political economist - Rafael Galv\~ao de Almeida (Duke University, Center for the History of Political Economy (CHOPE), 2019)
This article explores Douglass North's intellectual development as a political economist and an interdisciplinary researcher. Although he was an important figure during the cliometrics revolution, he later grew dissatisfied with the approach and went on to study institutions, helping to establish the New Institutional Economics. His political theory evolved with influences from Marxism and Public Choice Theory and is reflected in his work in the 1980s. His directorship at the Center in Political Economy at Washington University at St. Louis allowed him to work directly with other social scientists for the development of a New Political Economy.
Keywords: B25; D7; N01; 330